Hubungan Tawakal dan Ikhtiar dalam Kehidupan Bermasyarakat Perspektif Hadis: Studi Takhrij dan Syarah Hadis - Khalishah Sajidah (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about tawakal and endeavor. This study uses a qualitative approach by applying descriptive analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about tawakal and endeavor in the history of Bukhari no. 1930. The results and discussion of this study indicate that the status of hadith is of authentic quality that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Bukhari no. 1930 is relevant to be used as motivation, creativity, innovation, and the development of the field of trust and endeavor.